Socioeconomic impact of rice-cum-fish culture in a selected areas of Bangladesh (Journal of the Bangladesh Agricultural University, 2012)
The study examines the impact of the rice-cum-fish culture and the rice-mono culture on the rural households at  Muktaghachha upazila of Mymensingh district in Bangladesh. Data were collected from 100 farmers of five villages  following stratified random sampling technique. Activity budgets were prepared and comparisons were made through the tabular and statistical analyses. Both the rice-cum-fish culture and the rice-mono culture were profitable business  for the farmers. However, farmers earned about 3 times higher profits from the rice-cum-fish culture than the ricemono culture. Per hectare net returns of the rice-cum-fish culture and the rice-mono culture were Tk. 15345.00 and  5389.50, respectively. Rice yield, fish consumption, total cost were increased by 11.4, 14.5 and 48.9 percent  respectively while human labour employment was increased by 9.4 percent in the integrated rice-cum-fish culture compared to the rice-mono culture. The study clearly hints that the rice-cum-fish culture provides greater scope for higher returns and employment opportunities of human labour than the rice-mono culture. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12103 J. Bangladesh Agril. Univ. 10(1): 119123, 2012